Practical Validation of nearZEB Residential Power Supply Model with Renewable Electricity Brought into the Building Using Electric Vehicles (via V2G) Instead of the Distribution Network - Jacek A. Biskupski (Energies)
This article attempts to estimate the potential of supplying a residential building in Europe with energy exclusively from RESs during a whole year, including the heating period. The aim of the tests carried out was to minimize the purchase of energy required to achieve the thermal comfort (HVACR + DHW) of a residential building powered solely by electricity. During the tests carried out, the EVs were used by the residents as their daily means of transport, topped up during working hours, and the excess energy remaining in their batteries was discharged into the building when they returned home. Energy for the EVs/PHEVs was sourced from RESs (mostly for free) while they were parked at the workplace, and also on the way home. Two one-month tests in the spring and autumn resulted in a state where, instead of purchasing a significant volume of black energy from the grid, the building was mostly powered by green energy from roof-top PVs and RES energy brought in by the PHEVs/EVs. This study identified days when the building became a real nZEB, which was not possible in previous years. The results of economic gains and carbon footprint reduction were calculated. After a period of testing, the degree of degradation of traction batteries used to carry the energy of EVs/PHEVs was checked. A high potential for such an operation was identified, especially in areas where there are periodic shutdowns (due to a call from the grid operator) of local RESs situated near the residential areas. The proposed solution may be of interest to all countries where the use of grid energy is associated not only with a doubling of costs (grid charges), but also with significant emissions, particularly in the heating period (e.g., Poland).